Identification of a novel splice variant in SEC23B gene in a patient with concomitant presence of congenital dyserythropoietic anemia II and Gilbert’s syndrome - Woori Jang; Dong Jun Ha; Chung Hyun Nahm; Jisun Park; Su Jin Kim; Ji-Eun Lee; Yeonsook Moon (Hematology)
Background: Congenital dyserythropoietic anemia Ⅱ (CDA Ⅱ) is a rare inherited disorder of defective erythropoiesis caused by SEC23B gene mutation. CDA Ⅱ is often misdiagnosed as a more common type of clinically related anemia, or it remains undiagnosed due to phenotypic variability caused by the coexistence of inherited liver diseases, including Gilbert’s syndrome (GS) and hereditary hemochromatosis.Methods: We describe the case of a boy with genetically undetermined severe hemolytic anemia, hepatosplenomegaly, and gallstones whose diagnosis was achieved by targeted next generation sequencing.Results: Molecular analysis revealed a maternally inherited novel intronic variant and a paternally inherited missense variant, c.[994-3C > T];[1831C > T] in the SEC23B gene, confirming diagnosis of CDA Ⅱ. cDNA analysis verified that the splice acceptor site variant results in two mutant transcripts, one with an exon 9 skip and one in which exons 9 and 10 are deleted. SEC23B mRNA levels in the patient were lower than those in healthy controls. The patient was also homozygous for the UGT1A1*6 allele, consistent with GS.Conclusion: Identification of the novel splice variant in this study further expands the spectrum of known SEC23B gene mutations. Molecular genetic approaches can lead to accurate diagnosis and management of CDA Ⅱ patients, particularly for those with GS coexisting.